Intensive Hemodiafiltration Successfully Removes Ganciclovir Overdose and Largely Exceeds Reported Elimination During Hemodialysis—A Case Report and Review of the Literature - Gotta, Verena; Leuppi-Taegtmeyer, Anne; Gessler, Mirjam; Pfister, Marc; Müller, Daniel; Jehle, Andreas Werner (Frontiers in Pharmacology, 2020)
We present the case of a kidney transplant patient (Cockroft-Gault estimated creatinine clearance 14 mL/min) who was inadvertently 8-fold overdosed with a single dose of 500 mg intravenous ganciclovir. To prevent the immunosuppressed patient from being exposed to severe risks of prolonged ganciclovir overdosing, including potentially fatal bone marrow suppression and severe neurotoxicity, the patient was treated with hemodiafiltration (HDF) to enhance drug elimination. Since the product label reports a 50% decrease of ganciclovir plasma concentrations after intermittent hemodialysis (HD), two HDF sessions were considered necessary to achieve a ≥75% elimination of the drug by precaution, despite targeted intense HDF prescription. Ganciclovir plasma concentration data were obtained during both HDF sessions and were analysed retrospectively. Pharmacokinetic analysis revealed that prescribed HDF successfully decreased drug plasma concentrations by ≥90%. This ganciclovir reduction ratio matched the urea reduction ratio achieved (≥92%). Model-based assessment of ganciclovir dialysis clearance (estimated to be 445 mL/min), accounting for its 2-compartmental kinetics, was higher than urea dialysis clearance (estimated to be 310 mL/min). This suggests potential relevant accumulation of ganciclovir into blood cells, at least in this patient after overdosing. The amount (fraction) of drug removed by 1st HDF was estimated to 269 mg (93% of total amount of 288 mg eliminated during the 1st HDF session; estimated amount in the body prior to 1st HDF: 380 mg). A literature review was performed to summarize and systematically compare available information on ganciclovir elimination during intermittent renal replacement therapy. In conclusion, the high ganciclovir HDF clearance measured in our patient largely exceeded previously reported elimination during HD, meaning that HDF prescription was highly efficient in the present case, and that a second HDF session might not have been necessary. This finding may be considered to guide renal replacement therapy in the scope of drug overdosing. It may also be evaluated for ganciclovir dose adjustment in patients on chronic HD or HDF with high small solute clearance, since a strong correlation between ganciclovir and urea elimination efficiency was observed.